Najlepiej było by z obliczeniami razem ; ]]

Pomnóż jednomiany
a) 7x*3x=
b) 4x*3x²=
c) -2x*6x=
d) 2 ½x²*(-4x)=
e) -2x*(-8x)=
f) -⅓x³*30x=
g) -⅖x*3 ⅓x=
h) 0,3x²*1,5x²=
i) -1,2x*(-0,3x³)=
j) 2x³*(-3,8x)=
k) 4a²b*3ab²=
l) 7ab*6a²b=
m) -5a²b*(-3²b²)=
n) 8ab²*(-6ab²)=
o) 3½ab*¼a²b=
p) -0,7a²b*100ab=
r) 8xy²z³*2x²yz=
s) -3x²y²z*(-5xy²z)=
t) -6yz*(-0,4xy²z)=
u) -1 1/2x³y*0,6xz²=
w) 2/7xy²z³*2⅔x²y=
z) ⁶/¹¹x³y³z*(-5/3yz²)=

3

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-28T22:13:28+01:00
A) 7x*3x= 21x²
b) 4x*3x²= 12x³
c) -2x*6x= -12x²
d) 2 ½x²*(-4x)= -10x³
e) -2x*(-8x)= 16x²
f) -⅓x³*30x= -10x⁴
g) -⅖x*3 ⅓x= -1⅓x²
h) 0,3x²*1,5x²= 0,45x⁴
i) -1,2x*(-0,3x³)= 0,36x⁴
j) 2x³*(-3,8x)= -7,6x⁴
k) 4a²b*3ab²= 12a³b³
l) 7ab*6a²b= 42a³b²
m) -5a²b*(-3²b²)= 15a⁴b³
n) 8ab²*(-6ab²)= -48a²b⁴
o) 3½ab*¼a²b= ⅞a³b²
p) -0,7a²b*100ab= -70a³b²
r) 8xy²z³*2x²yz= 16x³y³z⁴
s) -3x²y²z*(-5xy²z)= 15x³y⁴z²
t) -6yz*(-0,4xy²z)= 2,4xy³z
u) -1 1/2x³y*0,6xz²= -0,9x⁴yz²
w) 2/7xy²z³*2⅔x²y= 16/21x³y³z³
z) ⁶/¹¹x³y³z*(-5/3yz²)= -10/11x³y⁴z³
7 4 7
2010-02-28T22:18:02+01:00
A) 7x*3x= 21x²

b) 4x*3x²= 12x³

c) -2x*6x= -12x²

d) 2 ½x²*(-4x)= -10x³

e) -2x*(-8x)= = 16x²

f) -⅓x³*30x= -10x^4 (do potegi czwartej)

g) -⅖x*3 ⅓x= -4/3 x² (cztery trzecie)

h) 0,3x²*1,5x²= 0,45x^4

i) -1,2x*(-0,3x³)= 0,36x^4

j) 2x³*(-3,8x)= -7,6x^4

k) 4a²b*3ab²= 12a³b³

l) 7ab*6a²b= 42a³b²

m) -5a²b*(-3²b²)= -5a²b*(9b²) = -45a²b³

n) 8ab²*(-6ab²)= -48a²b^4

o) 3½ab*¼a²b= 7/8 a³b² (siedem ósmych)

p) -0,7a²b*100ab= -70a³b²

r) 8xy²z³*2x²yz= 16x³y³z^4

s) -3x²y²z*(-5xy²z)= 15x³z²y^4

t) -6yz*(-0,4xy²z)= 2,4xy³z²

u) -1 1/2x³y*0,6xz²= -0,9yz²x^4

w) 2/7xy²z³*2⅔x²y= 16/21 x³y³z³

z) ⁶/¹¹x³y³z*(-5/3yz²)= -10/11x³z³y^4
4 5 4
  • Roma
  • Community Manager
2010-02-28T22:22:17+01:00
A) 7x*3x = 21x²

b) 4x*3x² = 12x³

c) -2x*6x = - 12x²

d) 2 ½x²*(-4x) = - 10x³

e) -2x*(-8x) = 16x²

f) -⅓x³*30x = - 10x⁴

g) -⅖x*3 ⅓x = - ⁴/₃ x² = - 1⅓x²

h) 0,3x²*1,5x² = 0,45x⁴

i) -1,2x*(-0,3x³) = 0,36x⁴

j) 2x³*(-3,8x) = - 7,6x⁴

k) 4a²b*3ab² = 12a³b³

l) 7ab*6a²b = 42a³b²

m) -5a²b*(-3²b²) = 45a²b³

n) 8ab²*(-6ab²) = - 48a²b⁴

o) 3½ab*¼a²b = ⁷/₈ a³b²

p) -0,7a²b*100ab = - 70a³b²

r) 8xy²z³*2x²yz = 16x³y³z⁴

s) -3x²y²z*(-5xy²z) = 15x³y⁴z²

t) -6yz*(-0,4xy²z) = 2,4xy³z²

u) -1½x³y*0,6xz² = - 0,9x⁴yz²

w) ²/₇xy²z³*2⅔x²y = ¹⁶/₂₁x³y³z³

z) ⁶/₁₁x³y³z*(-⁵/₃yz²) = - ¹⁰/₁₁x³y³z³